Internal medicine specialists' attitudes towards working part-time: a comparison between 1996 and 2004 - de Jong Judith D; Heiligers Phil JM; Lugtenberg Marjolein; Hingstman Lammert (BMC, 2006)
Abstract Background Although medical specialists traditionally hold negative views towards working part-time, the practice of medicine has evolved. Given the trend towards more part-time work and that there is no evidence that it compromises the quality of care, attitudes towards part-time work may have changed as well in recent years. The aim of this paper was to examine the possible changes in attitudes towards part-time work among specialists in internal medicine between 1996 and 2004. Moreover, we wanted to determine whether these attitudes were associated with individual characteristics (age, gender, investments in work) and whether attitudes of specialists within a partnership showed more resemblance than specialists' attitudes from different partnerships. Methods Two samples were used in this study: data of a survey conducted in 1996 and in 2004. After selecting internal medicine specialists working in general hospitals in The Netherlands, the sample consisted of 219 specialists in 1996 and 363 specialists in 2004. They were sent a questionnaire, including topics on the attitudes towards part-time work. Results Internal medicine specialists' attitudes towards working part-time became slightly more positive between 1996 and 2004. Full-time working specialists in 2004 still expressed concerns regarding the investments of part-timers in overhead tasks, the flexibility of task division, efficiency, communication and continuity of care. In 1996 gender was the only predictor of the attitude, in 2004 being a full- or a part-timer, age and the time invested in work were associated with this attitude. Furthermore, specialists' attitudes were not found to cluster much within partnerships. Conclusion In spite of the increasing number of specialists working or preferring to work part-time, part-time practice among internal medicine specialists seems not to be fully accepted. The results indicate that the attitudes are no longer gender based, but are associated with age and work aspects such as the number of hours worked. Though there is little evidence to support them, negative ideas about the consequences of part-time work for the quality of care still exist. Policy should be aimed at removing the organisational difficulties related to part-time work and create a system in which part-time practice is fully integrated and accepted.